MARCEL PROUST AND THE CHARACTERS OF JEWS IN THE NOVEL IN SEARCH OF LOST TIME (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
Independently of the imaginary individuality of the work of art that separates it from the reality, even by reason of his personal history, Marcel Proust is predestined to raise the question of the Jewishness: its origins (a Catholic father and a Jewish mother) incite him to focus on the Jewish question, but at the same time they cause the duplication of its position, allowing him a critical distance. The historical contingency makes his life history cross with a well-known fact, the Dreyfus affair, which created in him the sense of belonging to the Jewish people and imposed the question of essential signs of recognition of this people. With Swann, Bloch, and also Albertine and Rachel, Proust begins the narrative adventure which must respond to the question regarding all the faces of one of the ethnicities, the Jewishness. Keywords: Proust, Jewishness, Dreyfus affair, identity prophecy, art.